القباب ومناطق الانتقال في العمارة الدينية بالجزائر خلال العصر العثماني - بوزرينة, السعيد (University of Eloued جامعة الوادي, 2022)
تنوعت القباب ومراكز الانتقال في العمارة الدينية بالجزائر خلال العصر العثماني، وعلى غرار الطراز المحلي الموروث، هناك طراز وافد الذي جلب من تركيا يتمثل في القبة المركزية المضلعة الضخلة الأكثر استعمالا، حيث نجدها في المساجد والجوامع والزوايا كجامع صفر بن عبد الله جامع صفر بن عبد الله، وجامع كتشاوة الأصلي، وجامع الداي (القصبة الداخلي) وجامع الباشا بوهران وجامع صالح باي بعنابة وفي زاوية سيدي عبد الرحمن الثعالبي، وقاعة الضريح لزاوية سيدي أحمد بن يوسف وقاعة الضريح لزاوية تماسين بتقرت وفي الزاوية المختارية ببسكرة. Abstract: Domes and transition centers varied in religious architecture in Algeria during the Ottoman era, and on Similar to the local inherited style, there is an imported style that was brought from Turkey, which is the dome The polygonal central is the most widely used polygon, as we find it in mosques and mosques as a mosque Safar ibn Abdullah, the mosque of Safar ibn Abdullah, the original Jami 'Katshawa, and the al-Dai mosque (al-Kasbah Al-Dakhli), the Pasha Mosque in Oran, the Salih Bey mosque in Annaba, and in the corner of Sidi Abd al-Rahman al-Tha'albi,The mausoleum hall is for Zawiya Sidi Ahmed bin Youssef, and the mausoleum hall is for Zawiyat Tamasin, Btqret, and in the corner Al-Mukhtariah Biskra
مقال